The Effect of Managerial Ownership, Institutional Ownership and Corporate Social Responsibility (CSR) on Corporate Financial Performance in Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange - Wardani, Tiara Kusuma; Nurbaiti, Beti; Ningrum, Endah Prawesti; Nuryati, Tutty; Yulaeli, Tri (PT.KARYA GEMAH RIPAH, 2025)
This research aims to examine the influence of managerial ownership, institutional ownership and corporate social responsibility (CSR) on financial performance. The population in this research are all Property and Real Estate Issuer Companies Listed on the Indonesia Stock Exchange for the 2021 - 2023 Period. The variables used in this research are Managerial Ownership, Institutional Ownership and Corporate Social Responsibility (CSR) as the dependent variable and Financial Performance as the variable independent. The sampling technique used was the purposive sampling method and a total of 146 company samples were obtained. The analytical methods used are Descriptive Statistical Analysis, Classical Assumptions, Multiple Linear Analysis and Hypothesis Testing. The results of this research show that partially Managerial Ownership has a negative effect on Financial Performance, Institutional Ownership has a negative effect on Financial Performance and Corporate Social Responsibility (CSR) has no effect on Financial Performance. The research results simultaneously show that Managerial Ownership, Institutional Ownership and Corporate Social Responsibility (CSR) influence the Company's Financial Performance.